Co-existence of EGFR T790M-acquired lung adenocarcinoma and transformation into small-cell carcinoma in different organs after osimertinib treatment. A case report - Takeda, Masahide; Asano, Mariko; Sakamoto, Sho; Izumiya, Yuka; Okuda, Yuji; Sato, Kazuhiro; Nakayama, Katsutoshi (Current problems in cancer. Case reports, 2025)
•This case reports co-existing T790M-positive adenocarcinoma and T790M-negative small-cell carcinoma transformation in different organs after osimertinib treatment.•Cytology and biopsy findings highlighted the importance of re-biopsy in identifying resistance mechanisms in EGFR-mutated lung cancer.•Rechallenge with osimertinib successfully controlled pericardial effusion despite progressive mediastinal lymphadenopathy.•Immunohistochemical analysis revealed loss of RB1 as potential drivers of small-cell carcinoma transformation.•This rare case emphasizes the need for personalized treatment strategies in managing dual histologic transformation in lung cancer. We report a rare case of a 59-year-old man with EGFR-mutated lung adenocarcinoma who developed osimertinib resistance, with coexisting T790M-positive adenocarcinoma and T790M-negative small-cell carcinoma in different organs. After treatment with gefitinib, chemotherapy, osimertinib, and subsequent chemotherapy, the patient presented with progressive disease, including pericardial effusion and mediastinal lymphadenopathy. Cytology of the pericardial fluid confirmed adenocarcinoma, while lymph node biopsy revealed transformation to small-cell carcinoma. Rechallenge with osimertinib successfully controlled the pericardial effusion, but the disease ultimately progressed. This case emphasizes the importance of re-biopsy for understanding resistance mechanisms and highlights the challenges of managing dual histologic transformation in lung cancer, particularly when transformation to small-cell carcinoma occurs in different anatomical sites.